Quasi-Affineness and the 1-Resolution Property. (8th July 2020) - Deshmukh, Neeraj; Hogadi, Amit; Mathur, Siddharth
Abstract: We prove that, under mild hypothesis, every normal algebraic space that satisfies the 1 -resolution property is quasi-affine. More generally, we show that for algebraic stacks satisfying similar hypotheses, the 1-resolution property guarantees the existence of a finite flat cover by a quasi-affine scheme.